Liver fibrosis assessment by FibroScan compared with pathological findings of liver resection specimen in hepatitis C infection. Issue 8 (3rd October 2016) - Nakamura, Yuki; Aikata, Hiroshi; Fukuhara, Takayuki; Honda, Fumi; Morio, Kei; Morio, Reona; Hatooka, Masahiro; Kobayashi, Tomoki; Nagaoki, Yuko; Kawaoka, Tomokazu; Tsuge, Masataka; Hiramatsu, Akira; et al.
Abstract : Aim: FibroScan is a tool for the non‐invasive diagnosis of hepatic fibrosis. Previous studies have compared liver stiffness to percutaneous liver biopsy findings, but no study has compared liver stiffness to liver resection specimen findings. The aim of this study was to compare FibroScan measurements to resected liver specimen findings. Methods: From April 2011 to November 2015, a total of 114 patients with liver tumor and hepatitis C were enrolled. We divided them into two groups, the training set and validation set. Liver stiffness was measured by FibroScan before surgery, and specimens obtained by liver resection were evaluated according to the METAVIR system. Results: Using Spearman's rank correlation analysis, a positive correlation between liver stiffness measurement and liver fibrosis stage was observed ( r = 0.786, P ≤ 0.0001). In the training set, the area under receiver operating curves for diagnosis of F ≥ 2 was 0.971 (95% confidence interval, 0.928–1.000; cut‐off value, 5.9), for diagnosis of F ≥ 3 was 0.911 (0.825–0.997, 9.8), and for diagnosis of F = 4 was 0.917 (0.849–0.985, 15.5). In the validation set, at a cut‐off value of 5.9 kPa, sensitivity, specificity, positive predictive values, and negative predictive values for F ≥ 2 were 95.7%, 0.0%, 97.8%, and 0.0%, respectively, of 9.8 kPa for F ≥ 3 were 86.2%, 52.6%, 73.5%, and 71.4%, and of 15.5 kPa for F = 4 were 100%, 71.8%, 45.0%, and 100%. Conclusions: The stage of stiffness graded by FibroScan has a good correlation with the liver fibrosis of resected liver specimens. It has the ability to diagnose fibrosis stage non‐invasively.